Urinary dipeptidyl peptidase‐4 protein is increased by linagliptin and is a potential predictive marker of urine albumin‐to‐creatinine ratio reduction in patients with type 2 diabetes. Issue 8 (6th May 2021) - Klein, Thomas; Tammen, Harald; Mark, Michael; Benetti, Elisa; Delić, Denis; Schepers, Cornelia; von Eynatten, Maximilian
Abstract: Results of a post hoc analysis of urinary dipeptidyl peptidase‐4 (DPP‐4) protein as a predictor of urine albumin‐to‐creatinine ratio (UACR) response to linagliptin treatment based on MARLINA‐T2D trial data are described. MARLINA was a 24‐week, phase 3b, multinational, placebo‐controlled clinical trial, in which patients with type 2 diabetes (T2D), HbA1c 6.5%‐10.0% and UACR 30‐3000 mg/g ( n = 360) were treated with linagliptin or placebo. After 24 weeks of treatment, linagliptin significantly inhibited urinary DPP‐4 activity and increased urinary DPP‐4 protein. Furthermore, medium urinary DPP‐4 protein levels (between 5.5 and 7.5 natural logarithmic [ln] μg/g creatinine) at baseline allowed for prediction of improved UACR in linagliptin‐treated individuals. In patients with lower or higher levels of urinary DPP‐4 protein at baseline, no association between linagliptin treatment and improved UACR was present. This might suggest a varying degree of importance of DPP‐4 as a pathophysiological factor in T2D‐associated kidney disease. In summary, urinary DPP‐4 might be a useful predictive biomarker for UACR improvement by linagliptin.